2020
DOI: 10.1002/1878-0261.12849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genomic features associated with in vitro response of the NCI‐60 cancer cell line panel to natural products

Abstract: Natural products provide new opportunities for anticancer chemotherapeutics. We examined the associations of molecular features in the NCI‐60 cancer cell lines with response to 1302 plant, marine, and microbial compounds. Expression or mutations in multiple genes were associated with treatment responses, suggesting potential mechanisms of action of natural compounds. This information will assist in future design of new chemotherapy agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 154 publications
(263 reference statements)
2
13
0
Order By: Relevance
“…Alternative strategies leveraging this metabolic addiction have also been demonstrated via inhibiting glucose uptake preventing the conversion of potentially toxic cystine to cysteine [ 38 , 43 ]. This highly positive correlation (Spearman correlation coefficient ρ = 0.79, unadjusted p value = 1.07 × 10 –13 , FDR adjusted p value = 8.47 × 10 –8 ) demonstrates increased resistance of tumor cell lines to plumbagin associated with increased gene expression of SLC7A11, which is consistent with the previous findings by our group and other authors about the potential role of this transporter in resistance to multiple antitumor agents and natural products [ 29 , 38 , 42 , 44 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Alternative strategies leveraging this metabolic addiction have also been demonstrated via inhibiting glucose uptake preventing the conversion of potentially toxic cystine to cysteine [ 38 , 43 ]. This highly positive correlation (Spearman correlation coefficient ρ = 0.79, unadjusted p value = 1.07 × 10 –13 , FDR adjusted p value = 8.47 × 10 –8 ) demonstrates increased resistance of tumor cell lines to plumbagin associated with increased gene expression of SLC7A11, which is consistent with the previous findings by our group and other authors about the potential role of this transporter in resistance to multiple antitumor agents and natural products [ 29 , 38 , 42 , 44 ].…”
Section: Resultssupporting
confidence: 91%
“…Pre-treatment gene expression data for the NCI-60 cell lines was downloaded from the CellMinerCDB resource [ 23 , 28 ]. A more detailed description of the collection of molecular measures can be found in our previous publication [ 29 ]. For expression analysis, we used log 2 transformed expression measures of 23,059 annotated transcripts, lncRNAs, and miRNAs which had been previously combined from five Affymetrix expression microarray platforms and normalized by the CellMiner development team [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 The flexibility of this tool allows correlation analysis for specific cancer cell lines, such as the specific tool focused on small cell lung cancer cell lines (SCLC-CellMiner) developed by Tlemsani et al 47 Recently, Krushkal et al, considering the importance of natural sources for new possible lead compounds, correlated the GI 50 values and protein expression data stored in NCI and CellMiner to elucidate the potential mechanism of action of numerous natural products (extracted from plants, marine invertebrates, and microbes). 48 The lack of recurring updates of the CellMiner database induced Arroyo and co-workers to download all the available data from NCI-60 and undertake large-scale screening to find a connection between standardized cancer cell line sensitivity to antiproliferative agents and corresponding standardized protein expression. The results obtained showed that the correlation between the antiproliferative activity of a given drug and the expression of a given protein could be exploited to: (i) confirm the biological target of known drugs; (ii) associate a mechanism of action with a new small molecule; (iii) repurpose an already developed drug against another target with which it is 'correlated'; (iv) explain the pleiotropic effects of drugs (multi/offtarget view); and (v) find targets that can be influenced by a given drug.…”
Section: In Silico Approaches Based On the Correlation Between Cell Line Chemosensitivity And Gene/protein Expression Patternmentioning
confidence: 99%
“…Several thousand years ago, natural products were used for their medicinal properties (6), and increasing evidence has shown that natural products from vegetables, fruits and traditional medicines for anti-cancer research remains an important source of potentially novel treatments (7)(8)(9)(10)(11). Although there was a shift towards the study of synthetic drugs based on molecular biology and combinatorial chemistry, these synthetic drugs have the disadvantages of occasional intolerable side effects and expensive prices (12,13).…”
Section: Introductionmentioning
confidence: 99%